The role of brain wave activity by electroencephalogram (EEG) in assessing cognitive skills as an indicator for driving fatigue: A review - Kamat, Seri Rahayu; Ibrahim, Muhammad Shafiq; Shamsuddin, Syamimi (Penerbit Akademia Baru, 2023)
A number of studies have employed EEG to investigate the relationship betweenbrain wave activity and fatigue. However, research on the relationship between brain wave activity and cognitive skills in detecting driving fatigue is scarce. This study thoroughly summarizesprevious studies on electroencephalogram (EEG)-based brain wave activity and how tolink it to cognitive skills as an indicator of driving fatigue. A thorough systematic literature review (SLR) was used to identify strong and high-potential material linked to the research topic. When a person went from alert to fatigue, alpha and theta waves increased while beta waves decreased. Alpha, thetaand beta have previously been linked to attention, working memory capacityand decision making. As a result, if alpha and theta waves increase but beta waves drop, a person may become fatigued, indicating significant cognitive impairment in that individual. The misunderstanding about how brain activity changes when a person fatigues among the studies could be attributed to the use of a small number of participants and the number of electrodes used to assess EEG change. The study's findings will assist researchers, policymakers, and practitioners in developing a system that will greatly reduce fatigue-related traffic accidents, thereby improving road safety.